One size doesn't fit all : serving special populations, workforce challenges, service delivery and policy implications : insights from practitioners and academics - Malka, S. Charles; Tiell, Robert H. (Emerald Publishing Limited, 2025)
Current and future societal developments are likely to affect various populations differently. Tectonic shifts, new or accelerated by Covid-19, have affected many populations in distinctively different ways that cannot be ignored given their collective impact on workforces and workplaces alike. Their story must be told. The USA's changing demographics also must be considered. Based on US Census data, by the year 2045, the nation is expected to become a minority majority country. In other words, all minorities when bundled together will then become a majority for the first time in US history. This in turn will have significant implications for large segments of society, including service providers who specialize and work closely with many of these different populations. Diversity will be manifested in a variety of ways. It is essential as a society to stop and consider what this means for delivering quality services to so many different populations, each one of which will likely present with its own unique set of circumstances, dynamics, and needs that must be examined and addressed. One Size Doesn't Fit All is unique in addressing this issue and doing so in such a way that maximizes the positive impact these special populations can have on the service delivery system and the country's future economic well-being. It offers a service-delivery-driven, "best-practices" approach for working with diverse, special populations, with each chapter focusing on a different yet important population. One Size Doesn't Fit All readily assists practitioners and policy makers with how they might best serve the emerging needs of many different populations with whom they likely interact, serve, direct, and/or fund.